Auditor reputation and sharia bond ratings: Evidence from Indonesia - Pandansari, Tiara (JIFA (Journal of Islamic Finance and Accounting), 2022)
Sharia bonds, a segment within the realm of Islamic finance, has demonstrated significant growth over the last decade, emerging as one of the fastest-growing sectors in the industry. This study aimed to analyze the effect of liquidity, profitability, leverage, maturity, and auditor's reputation on sharia bonds ratings. The data collection method used is secondary data sourced from the company's financial statements. The population in this study are companies that issue sharia bonds on the Indonesia Stock Exchange. Sampling using the purposive sampling method with 17 with certain criteria. The data were analyzed using SPSS version 22. The analysis used is ordinal logistic regression analysis. The results showed that liquidity and leverage had no effect on the sharia bond's rating. The profitability, maturity, and reputation of auditors negatively affect the rating of sharia bonds. Sharia-compliant bonds, also known as Sukuk, have a substantial impact on the Islamic finance sector and contribute to the advancement of the global Islamic banking and finance industry. These bonds serve as a means for governments, corporations, and institutions to secure capital while adhering to the principles of Sharia law. They attract investors who prioritize investments that align with their religious beliefs and ethical values.